Relationship between platelet parameters and sudden sensorineural hearing loss: a systematic review and meta-analysis. Issue 6 (14th November 2018) - Ji, Shuaifei; Chen, Xuemin; Shi, Heng; Zhang, Babo; Yao, Shun; Deng, Senlin; Tian, Chunlong; Jiang, Jun; Chen, Fei; Wang, Xiaocheng
Abstract : Recent years, the discussion about whether platelets participant in the development of sudden sensorineural hearing loss (SSHL) continues and many studies on the relationship between them have come to our attention. Some studies believe that platelet parameters have significantly changed in patients with SSHL, while some not, controversially. Therefore, to investigate the association between platelet parameters, including mean platelet volume (MPV), platelet distribution width (PDW) and platelet count (PLT), and SSHL, expecting to resolve controversy and provide clinical evidence for diagnosis and monitoring of SSHL. Basic methods: Literature was retrieved searching electronic databases (PubMed, Embase, Cochrane, and Scopus) and searching references of related articles by hand. A total of 18 case–control studies involving 1837/1734 subjects (SSHL/control) were included. Meta-analysis showed there was no difference between the patients who suffered SSHL and healthy controls in MPV level [standard mean difference (SMD) (95% confidence interval (CI)) = 0.16 (−0.07, 0.40), I 2 = 80%, P <0.00001] and PLT [SMD (95% CI) = −0.03(−0.18, 0.12), I 2 = 73%, P <0.00001]. While PDW exhibited significant difference [SMD (95% CI) = 0.85 (0.20, 1.49), I 2 = 93%, P <0.00001]. Subgroup analysis about geographical area suggested PLT have obvious evidence for SSHL in Eastern country [SMD (95% CI) = 0.23 (0.14, 0.33), I 2 = 0%, P =0.81]. Our study did not support a correlation between MPV and SSHL, while PLT may have clinical significance for SSHL in Eastern country. With insufficient data to explore the resource of heterogeneity for PDW, there is no decisive conclusion reached.